Tone Burst Electrocochleography for the Diagnosis of Clinically Certain Meniere's Disease - Hornibrook, Jeremy (Frontiers in Neuroscience, 2017)
The technique of transtympanic electrocochleography was initially developed as an objective hearing threshold test by Eggermont. Gibson et al. (1977) claimed that an enlarged direct current component of the action potential (AP) called the summating potential (SP) is an indication of endolymphatic hydrops, later confirmed by Coates who proposed an SP/AP ratio measure. This led to numerous publications using diagnostic ratios of 0.33–0.35. The insensitivity led to an eventual disenchantment with the test as a reliable objective test for Meniere's disease. It was further confused by audiologists employing remote canal or ear drum electrodes which give a response about one-fourth of the magnitude obtained by an electrode in contact with the cochlea. Subsequently Gibson stated that an SP/AP ratio of <0.5 is not diagnostic for hydrops. He then showed that a tone burst stimulus gave the test a significantly higher sensitivity and specificity, which has been supported by others. On MRI inner ear imaging with gadolinium hydrops can be seen, but the quality of images and what is seen may vary according to brand of scanner, settings, mode of gadolinium administration, and the possibility that gadolinium entry may favor the vestibule. Transtympanic tone burst electrocochleography is to date the simplest, cheapest and most sensitive technique for detecting cochlear endolymphatic hydrops to confirm a diagnosis of Meniere's disease.